Wives' Soft Skills in Relation to the Family Economics - Aninam, Johny; Parinusa, Sisilia M.; Sawaki, Magriet E. (AIBPM Publisher, 2023)
The transformation of gender roles in recent decades has brought significant changes to the dynamics of family economics. Specifically, attention to the role of wives is not only focused on financial contributions but also on the recognition of their soft skills. This research explores the relationship between the soft skills of wives and various aspects of family economics. This study highlights the role of soft skills, including effective communication, time management, adaptability, leadership, and emotional intelligence, in shaping the sustainability of family economics. The research employs a literature review method. The results of the study indicate that good communication skills facilitate open dialogue, time management, and multitasking abilities are crucial for the balance of wives' roles. Adaptability and problem-solving skills provide resilience to economic challenges. Leadership and decision-making by wives contribute to the direction of family economics, while emotional intelligence helps create a harmonious family environment. The importance of a deep understanding of the role of wives' soft skills in the context of family economics is emphasized in this research. The findings provide valuable insights for decision-makers, marketing professionals, and other stakeholders to understand how improving soft skills can have a positive impact on financial decisions, family dynamics, and overall well-being.